The Molecular Properties and Roles of Pannier in Harmonia axyridis’s Metamorphosis and Melanin Synthesis - Tian, Renbin; Chen, Xu; Wu, Mengmeng; Xu, Qingxuan; Wang, Su; Zang, Liansheng; Xiao, Da (Frontiers in Physiology, 2022)
The GATA transcription factor Pannier is identified as the major regulatory gene in color pattern formation in the Asian multi-colored ladybird beetle (Harmonia axyridis), however, mechanisms of Pannier in regulate melanin synthesis and development in H. axyridis remain elusive. In this study, we identified and characterized HaPnr in H. axyridis and showed it has two alternative spliced variants named HaPnr-α and HaPnr-β. Analyses of developmental stage expression patterns revealed that HaPnr, HaPnr-α and HaPnr-β were constitutively expression throughout all developmental stages. To examine the role of HaPnr in H. axyridis development, RNA interference was performed in late larvae and early pupae. We further demonstrated that suppression of HaPnr-α or HaPnr-β individually did not affect pupation and eclosion process. Suppression of HaPnr-α expression resulted in elytra melanin decreased in both the conspicua and succinea subgroup in H. axyridis. Even though suppression of HaPnr-β expression only affect the melanin synthesis in succinea subgroup, but significantly prolong the time of melanin synthesis in conspicua subgroup in H. axyridis. These results indicate that HaPnr plays an essential role in insect development, especially during their metamorphosis and support our conclusion that HaPnr could regulate melanin synthesis in H. axyridis under the combined action with its two splicing variants HaPnr-α and HaPnr-β.